Analysis of How the Intermediary Role Will Change in the Future with Globalization and the Increasing Power of Spread of IT, Particularly Cloud Based Technology - NIU, QING (2016)
Intermediaries, as the important role in supply chain, perform a series of functions, including assisting sellers in determining product offerings, helping buyers reduce the search cost and search time, and shipping, distributing and storing for products. However, with the advent of internet, there are IT platforms based on e-commerce and cloud manufacturing, to act as intermediary in supply chain. For example, Amazon.com, FMG.com and Alibaba, the popular e-marketplaces, have the function to match buyers and sellers and facilitate the transactions, which has negative effects on the roles and functions of intermediaries. Based on the advanced technology, “i5 system” created by SYMG (a Chinese corporation) and CAPP-4-SMEs project also challenge the roles and functions of intermediaries. Nevertheless, these IT platforms also face with issues, such as trust fraud and intellectual property protection.